Determinants of state fragility and implications for aid allocation: An assessment based on the country indicators for foreign policy project - David Carment; Stewart Prest; Yiagadeesen Samy (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
This paper is derived from our ongoing research on fragile states funded by the Canadian International Development Agency (CIDA) to help policymakers and analysts make decisions on where and how to allocate aid, especially in fragile state environments. In order for development assistance to have a measurable and positive impact on fragile states, it is necessary to understand both how and why they become fragile. First, we reconceptualize the meaning of state fragility with equal attention given to the authority, legitimacy and capacity of a state, collectively referred to as ALC. Measures of these ALC components corresponding to.
Keywords: F35; O10; O11; 330; foreign aid; fragile states; Staatskrise; Entwicklungshilfe